PERBEDAAN PENDAPAT DI SEKITAR KEDATANGAN AGAMA ISLAM DI INDONESIA - Suwedi Montana (BRIN, 1994)
The arrival of Islam in Indonesia has been widely debated and often discussed. The meaning of arrival here is the initial spread or early influence of Islam in Indonesia. The influnece can be brought by individual or by groups. Nearly two decades, the seminar on the Islamic diaspora were three times discussed. Two times in Medan and Aceh, respectively in 1963 and 1978, and the third seminar in Perlak in 1981. Meanwhile, other experts, both an orientalist and the historians of Islam of the late XIX CE and early XX CE, also other independent researchers, conduct individual research on the arrival of Islam in Indonesia. They freely state the results of their research. Therefore in this paper we will look at how far these opinions and views are connected by proving them in convincing arguments.